Clinafloxacin Pharmacokinetics in Subjects with Various Degrees of Renal Function - Randinitis, Edward J. (American Society for Microbiology, 2001)
As the primary route for elimination of clinafloxacin is renal clearance (CL(R)) of unchanged drug, studies were conducted to determine the pharmacokinetic profile of clinafloxacin following administration to young and elderly subjects, subjects with various degrees of renal function, and subjects requiring dialysis. These were open-label studies in which subjects received single oral clinafloxacin doses. Sixteen young subjects (18 to 35 years old) and 16 elderly subjects (>65 years old) were enrolled in a study comparing pharmacokinetic profiles of clinafloxacin in young and elderly subjects. Twenty subjects having various degrees of renal function were enrolled into one of three groups based on degree of renal function as measured by creatinine clearance (CL(CR)). Twelve subjects with severe renal impairment requiring dialysis enrolled in a third study. Clinafloxacin was generally well tolerated by all subjects. Clinafloxacin pharmacokinetic profiles in elderly subjects were dependent only on age-related decreases in renal function. Clinafloxacin maximum concentrations in plasma, areas under the concentration-time curves, and terminal elimination half-life values increased with decreasing CL(CR) values. Total apparent body clearance of clinafloxacin from the plasma after oral administration (CL(oral)) and CL(R) were dependent on CL(CR) according to the following relationships: CL(oral) = 2.3 · CL(CR) + 77 and CL(R) = 1.74 · CL(CR). Hemodialysis had no significant effect on clinafloxacin clearance. Based on the relationship between CL(CR) and clinafloxacin CL(oral) and CL(R) values, the clinafloxacin dose should be halved in patients having a CL(CR) of <40 ml/min. Further dose adjustment is not warranted in patients requiring hemodialysis.